# Thursday October 24 ## Conjugates Let $E\geq F$. Then $\alpha, \beta \in E$ are **conjugate** iff $\min(\alpha, F) = \min(\beta, F)$. *Example:* $\alpha \pm bi \in \CC$. **Theorem:** Let $F$ be a field and $\alpha, \beta \in F$ with $\deg \min (\alpha, F) = \deg \min (\beta, F)$, so \begin{align*} [F(\alpha): F] = [F(\beta): F] .\end{align*} Then $\alpha, \beta$ are conjugates $\iff$ $F(\alpha) \cong F(\beta)$ under the *conjugation map*, \begin{align*} \psi: F(\alpha) &\to F(\beta) \\ \sum_{i=1}^{n-1} a_i \alpha^i &\mapsto \sum_{i=1}^{n-1} a_i \beta^i .\end{align*} *Proof:* $\impliedby$: Suppose that $\psi$ is an isomorphism. Let $\min(\alpha, F) = p(x) = \sum c_i x^i$ where each $c_i \in F$. Then \begin{align*} 0 = \psi(0) = \psi(p(\alpha)) = p(\beta) \implies \min(\beta, F) \divides \min(\alpha, F) .\end{align*} Applying the same argument to $q(x) = \min(\beta, F)$ yields $\min(\beta, F) = \min(\alpha, F)$. $\implies$: Suppose $\alpha, \beta$ are conjugates. *Exercise:* Check that $\psi$ is surjective and \begin{align*} \psi(x+y) = \psi(x) + \psi(y) \\ \psi(xy) = \psi(x) \psi(y) .\end{align*} Let $z = \sum a_i \alpha^i$. Supposing that $\psi(z) = 0$, we have $\sum a_i \beta^i = 0$. By linear independence, this forces $a_i = 0$ for all $i$, and thus $z=0$. So $\psi$ is injective. $\qed$ **Corollary:** Let $\alpha \in \overline F$ be algebraic. Then 1. Any $\phi: F(\alpha) \injects \overline F$ such that $\phi(f) = f$ for all $f\in F$ must map $\alpha$ to a conjugate. 2. If $\beta \in \overline F$ is a conjugate of $\alpha$, then there exists an isomorphism $\phi: F(\alpha) \to F(\beta) \subseteq \overline F$ such that $\phi(f) = f$ for all $f\in F$. *Proof of 1:* Let $\min(\alpha, F) = p(x) = \sum a_i x^i$. Note that $0 = \psi(p(\alpha)) = p(\psi(\alpha))$, and since $p$ was irreducible, $p$ must also be the minimal polynomial of $\psi(\alpha)$. Thus $\psi(\alpha)$ is a conjugate of $\alpha$. $\qed$ *Proof of 2:* $F(\alpha)$ is generated by $F$ and $\alpha$, and $\psi$ is completely determined by where it sends $F$ and $\alpha$. This shows uniquness. $\qed$ **Corollary:** Let $f(x) \in \RR[x]$ and suppose $f(a+bi)= 0$. Then $f(a-bi) = 0$. *Proof:* Both $i, -i$ are conjugates and $\min(i, \RR) = \min(-i, \RR) = x^2 + 1 \in \RR[x]$. We then have a map \begin{align*} \psi: \RR[i] &\to \RR[-i] \\ \psi(a+bi) = a + b(-i) .\end{align*} So if $f(a+bi) = 0$, then $0 = \psi(f(a+bi)) = f(\psi(a+bi)) = f(a-bi)$. $\qed$